Investigating Students' Strategies and Methods in Translating English Text into Indonesian - Putra, Dhanu Ario; Rullyanti, Merry (UNIVED Press, Universitas Dehasen Bengkulu, 2023)
In this era, England plays an important role in all fields, especially in education. Someone demanded to know the meaning and function of an English word. Thus, translation is also one of the four skills of mastering the English language, in addition to listening, speaking, reading and writing, translation also has a main function. The purpose of this work was to find out if students are committed to translating an English text, to describe the method used by students in translating an English text, to observe the ability of the students to translate an English text. Therefore, this study seemed very suitable for a case study because it tried to explore and explore student strategies in one class of 23 students. In this study, the researcher administered the test to students. In the test technique, the researcher gave an English text and asked the students to translate the English text as best as possible. There are four criteria to evaluate a student's translation, they are accuracy of message content, distinctiveness of message, appropriateness of language use and lastly mechanical appropriateness. The researcher also interviewed the translation teacher who was considered a key informant who really knew how far the student's ability to translate an English text was. The result of the interview was given to the teacher; showed that the students of the 4th semester still had many difficulties, they used only one technique for translation. In particular, these words are rarely found in English textbooks. In addition, the lecturer must be creative to find a suitable translation method for the students of the 4th semester to translate the English text into Indonesian, also the lecturer always motivates the students to understand the text by translating the source language into their target language. Right in Indonesian. At the same time, the students also needed a longer time to practice the translation of the text from the English text to the Indonesian language, because they do not have the right method to translate the English text and the lack of vocabulary, although the lecturer. Had already practiced the practice of the English text, but it was not enough to interest the students in practicing the translation of the English text.